MicroRNA-Mediated Down-Regulation of M-CSF Receptor Contributes to Maturation of Mouse Monocyte-Derived Dendritic Cells - Riepsaame, Joey; van Oudenaren, Adri; den Broeder, Berlinda J. H.; van IJcken, Wilfred F. J.; Pothof, Joris; Leenen, Pieter J. M. (Frontiers in Immunology, 2013)
Dendritic cell (DC) maturation is a tightly regulated process that requires coordinated and timed developmental cues. Here we investigate whether microRNAs are involved in this process. We identify microRNAs in mouse GM-CSF-generated, monocyte-related DC (GM-DC) that are differentially expressed during both spontaneous and LPS-induced maturation and characterize M-CSF receptor (M-CSFR), encoded by the Csf1r gene, as a key target for microRNA-mediated regulation in the final step towards mature DC. MicroRNA-22, -34a and -155 are up-regulated in mature MHCIIhi CD86hi DC and mediate Csf1r mRNA and protein down-regulation. Experimental inhibition of Csf1r-targeting microRNAs in vitro results not only in sustained high level M-CSFR protein expression but also in impaired DC maturation upon stimulation by LPS. Accordingly, over-expression of Csf1r in GM-DC inhibits terminal differentiation. Taken together, these results show that developmentally regulated microRNAs control Csf1r expression, supplementing previously identified mechanisms that regulate its transcription and protein surface expression. Furthermore, our data indicate a novel function for Csf1r in mouse monocyte-derived DC, showing that down-regulation of M-CSFR expression is essential for final DC maturation.